Gold(I) N-heterocyclic carbene complexes with naphthalimide ligands as combined thioredoxin reductase inhibitors and DNA intercalators - Meyer, Andreas; Oehninger, Luciano; Geldmacher, Yvonne; Alborzinia, Hamed; Wölfl, Stefan; Sheldrick, William S.; Ott, Ingo (ChemMedChem, 2014)
Abstract Organometallic conjugates consisting of a gold(I) N-heterocyclic carbene (NHC) moiety and a naphthalimide were prepared and investigated as cytotoxic agents that interact with both DNA and the disulfide reductase enzyme thioredoxin reductase (TrxR). The complexes were potent DNA intercalators related to their naphthalimide partial structure, inhibited TrxR as a consequence of the incorporation of the gold(I) moiety, and triggered efficient cytotoxic effects in MCF-7 breast and HT-29 colon adenocarcinoma cells. Strong effects on tumor cell metabolism were noted for the most cytotoxic complex, chlorido[1-(3?-(4??-ethylthio-1??,8??-naphthalimid-N??-yl))-propyl-3-methyl-imidazol-2-ylidene]gold(I) (4?d). In conclusion, the conjugation of naphthalimides with gold(I) NHC moieties provided a useful strategy for the design of bioorganometallic anticancer agents with multiple modes of action.
Gesehen am 01.09.2020